Tracheostomy in 80 COVID-19 Patients: A Multicenter, Retrospective, Observational Study - Tang, Yun; Wu, Yongran; Zhu, Fangfang; Yang, Xiaobo; Huang, Chaolin; Hou, Guo; Xu, Wenhao; Hu, Ming; Zhang, Lu; Cheng, Aiguo; Xu, Zhengqin; Liu, Boyi; et al. (Frontiers in Medicine, 2020)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has led to a large and increasing number of patients requiring prolonged mechanical ventilation and tracheostomy. The indication and optimal timing of tracheostomy in COVID-19 patients are still unclear, and the outcomes about tracheostomy have not been extensively reported. We aimed to describe the clinical characteristics and outcomes of patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia who underwent elective tracheostomies. Methods: The multi-center, retrospective, observational study investigated all the COVID-19 patients who underwent elective tracheostomies in intensive care units (ICUs) of 23 hospitals in Hubei province, China, from January 8, 2020 to March 25, 2020. Demographic information, clinical characteristics, treatment, details of the tracheostomy procedure, successful weaning after tracheostomy, and living status were collected and analyzed. Data were compared between early tracheostomy patients (tracheostomy performed within 14 days of intubation) and late tracheostomy patients (tracheostomy performed after 14 days). Results: A total of 80 patients were included. The median duration from endotracheal intubation to tracheostomy was 17.5 [IQR 11.3-27.0] days. Most tracheotomies were performed by ICU physician (62 (77.5%)), and using percutaneous techniques (63 (78.8%)) at the ICU bedside (76 (95.0%)). The most common complication was tracheostoma bleeding (14 (17.5%)), and major bleeding occurred in 4 (5.0%) patients. At 60 days after intubation, 31 (38.8%) patients experienced successful weaning from ventilator, 17 (21.2%) patients discharged from ICU, and 43 (53.8%) patients had died. Higher 60-day mortality (22 (73.3%) vs 21 (42.0%)) were identified in patients who underwent early tracheostomy. Conclusions: In patients with SARS-CoV-2 pneumonia, tracheostomies were feasible to conduct by ICU physician at bedside with few major complications, and compared with tracheostomies conducted after 14 days of intubation, tracheostomies within 14 days were associated with an increased mortality rate.